2002
DOI: 10.1183/09031936.02.01832001
|View full text |Cite
|
Sign up to set email alerts
|

Asthma prevalence in children living in villages, cities and refugee camps in Palestine

Abstract: Previous studies have suggested that asthma prevalence is generally lower in the Middle East than in more developed countries. The aim of this study was to investigate the prevalence and severity of asthma and asthma symptoms in schoolchildren in the Ramallah District in Palestine.In the autumn of 2000, 3,382 schoolchildren aged 6-12 yrs were surveyed in 12 schools, using the International Study for Asthma and Allergies in Childhood (ISAAC)-phase III, parents-administered translated questionnaire.The crude pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Among children, the rates are also high and increasing. 33 Few patients with asthma use their inhaler devices correctly, with up to 75%, 43%, and 7% of patients incorrectly using MDI, Turbuhaler, and Diskus devices, respectively. 34 Basheti et al reported that, despite differences in Jordan's and Australia's health systems, pharmacists and patients from both countries had difficulty with using both Turbuhaler and Diskus devices correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Among children, the rates are also high and increasing. 33 Few patients with asthma use their inhaler devices correctly, with up to 75%, 43%, and 7% of patients incorrectly using MDI, Turbuhaler, and Diskus devices, respectively. 34 Basheti et al reported that, despite differences in Jordan's and Australia's health systems, pharmacists and patients from both countries had difficulty with using both Turbuhaler and Diskus devices correctly.…”
Section: Discussionmentioning
confidence: 99%
“…The initial prevalence and case-control studies have been described previously in detail (11,12). In brief, based on a parent-administered standardized questionnaire in 3,382 children 6 to 12 years of age 298 reported wheezing in the previous 12 months (cases).…”
Section: Study Design and Protocolsmentioning
confidence: 99%
“…As part of the International Study for Asthma and Allergies in Childhood (ISAAC), we have previously shown, in a cross-sectional study in the Ramallah district in Palestine, that the prevalence of wheeze in the past 12 months amounted to 8.2%, 7.2%, and 12.6% for children residing in villages, cities and refugee camps, respectively (11). Nested in this study, we carried out a case-control study to explore the as- sociations between a number of traditional risk factors and asthma (12).…”
Section: Introductionmentioning
confidence: 99%
“…Cairo is mainly an urban district surrounded by multiple industrialized areas and air pollution is one of the highest levels worldwide due to industrialization and heavy traffic, while Fayoum is a semi urban area surrounded by rural societies, and has less industrial areas 15 . In the Middle East, asthma prevalence was previously reported to be lower than in "developed" countries ranging from 5-23% [16][17][18][19] . In Gulf countries, bronchial asthma emerged to be one of the prevalent diseases especially in Saudi Arabia where asthma prevalence is approximately 24% 20 .…”
Section: Discussionmentioning
confidence: 99%